The use of adjacency pairs in a spontaneous group discussion with form six students - Clarice Joannes (2008)
Knowledge of interaction strategies is of utmost importance in determining a smooth flow of conversation or discussion. This study aimed to observe how interaction strategy training with explicit instruction of adjacency pairs might effect the development of conversational proficiency among low proficient learners. The target population involved in this study were low proficient Form Six students in one of the secondary schools at Kunak District. Samples taken had very limited vocabulary in English Language, thus they were unable to participate actively in group discussion and very reluctant to speak. This had caused low score for their MUET Speaking Test. In this study, adjacency pairs (question-answer) were introduced to these learners as a technique in collaborative learning. There were treatment and control groups involved in this study. The data were collected through direct observation. These learners were required to sit for pretest and posttest. It was revealed that after the training the treatment group had used more instances of interaction strategies compared to the control group. Question and answer form were most effectively used in maintaining conversation, selecting speaker and encouraging a reply. The findings showed that the treatment group were more confident in their discussion. They were always alert to the ongoing discussion because questions were posed at the end their speech. Therefore, from the findings of this study it did show that explicit instruction of adjacency pairs facilitates these learners in their discussion